A catalogue and bibliography of non-marine (freshwater and estuarine Rhodophyta (red algae) of India - Ganesan, E. K.; West, John A.; Necchi Jr, Orlando [UNESP] (Magnolia Press, 2018)
An annotated bibliographic catalogue of Indian red algae (Rhodophyta) occurring in freshwater and estuarine habitats (moist terrestrial soils, ponds, streams, rivers, lakes, large inland brackish water lagoons and coastal estuaries), based on more than a century (1846 to 2017) of publications is presented in a single coherent work for the first time. There have been 81 taxonomic entities (species, varieties and doubtful records), distributed among 21 genera recorded for the vast Indian sub-continent. Species distribution among the 21 genera are as follows: Audouinella-12; Balliopsis-1; Batrachospermum-11; Bosttychia-7; Caloglossa-8; Catenella-3; Chroodactvlon (including Asterocytis)-2; Chroothece-1; Compsopogon-8, Compsopogonopsis-1; Hildenbrandia-1; Kumanoa-7; Kyliniella-1; Lemanea-6; Nothocladus-1; Polysiphonia-1; Porphyridium-1; Sheathia-1; Sirodotia-4; Thorea-2; and Tuomeya-2. Of the seven currently recognized classes of Rhodophyta, no members of Bangiophyceae, Cyaniodiophyceae, or Rhodellophyceae are recorded from India. For each taxon, the following information is provided: (i) valid and currently accepted binomial (ii) synonyms as applicable to Indian records (iii) references with distribution in India and (iv) brief notes. Descriptions of new species based on Indian collections (holotypes) are indicated and some new combinations were made, when necessary. Several generic records (e.g., Balliopsis, Hildenbrandia, Kvliniella, Nothocladus and Tuomeya) and some species records (e.g. Batrachospermum longiarticulatum, Lemanea australis, L. catenata, L. fluviatilis, L. mamillosa, L. lorulosa and Thorea hispida) warrant detailed confirmatory data based on reinvestigation of fresh collections for morphology, reproduction and particularly molecular data to confirm the presence in the country. Future collections, especially in the Indian Biodiversity Hotspots (Indo-Burma, Western and Eastern Ghats and Andaman & Nicobar Islands), may uncover the occurrence of genera such as Bangia, Cyanidium and Nemalionopsis known to be present in neighbouring countries of Pakistan, Nepal and Thailand. Geothermal (acidic) hot water springs in India may reveal the presence of extremophilic unicellular red algal genera like Cyanidium, Cyanidioschvzon and Galdieria of the Cyanidiophyceae. Two maps showing the political and biogeographic zones of India are included. The need to preserve holotype and duplicate/voucher specimens with GPS data of future collections of red algal groups in a centralized national facility is also highlighted.
Keywords: Bibliographic Catalog; Non-Marine; Compsopogonophyceae; Freshwater; Estuarine; Florideophyceae; India; Red Algae